A systematic review of collaborative mobileassisted language learning (C-MALL) practices using bibliometric, content, and scientometric analyses - Guo, Pingping; Jeyaraj, Joanna Joseph; Razali, Abu Bakar (Springer Science and Business Media LLC, 2024)
The rapid proliferation of mobile technology and its widespread integration in education, particularly in language instruction and acquisition, as well as its effectiveness in facilitating collaborative learning, have recently sparked a surge in research focused on collaborative mobile-assisted language learning (C-MALL). This review sought to delineate the current landscape of literature on C-MALL practices, pinpoint research trends, and propose avenues for future research while providing valuable insights for C-MALL pedagogical strategies. To achieve this objective, the review adhered to the PRISMA protocol, analyzing 72 studies sourced from ﬁve databases following stringent inclusion and exclusion criteria. Key ﬁndings encompassed: (1) an escalating yearly publication trend on C-MALL practices, with a substantial spike observed post-2019; (2) a dominant contribution from Asian nations in terms of publication volume; (3) a prevalence of studies conducted in higher education settings employing mixed-method or quantitative methodologies on small sample sizes over short durations; (4) C-MALL designs predominantly leveraging social media collaborative learning platforms via smartphones; and (5) the most prominent keywords being motivation, writing, and engagement. The implications of these ﬁndings for both researchers and educational practitioners were thoroughly deliberated upon as per the review outcomes.